Stigma in Family Patients Who Have a Psychiatric Disorder: A Systematic Review - Antonia Rensiana Reong; Retno Puji Astuti (Jurnal Ners, 2019)
Introduction: The stigma in families who are caring for patients who experience mental illness in the modern era is high. Some of the experiences of patients with mental illness reveal that they are still stigmatized. This is not just the patients but also the families that care for them. The aim of this study was to conduct a systematic review relating to the stigma felt by the families of the patients experiencing mental illness.Methods: The database used  to identify the potential articles was Scopus. The articles were limited to a range of 5 years from 2014 through to 2018. The keywords used in the literature review were "Stigma Family" And "Mental illness".Results: Fifteen articles from eight countries were evaluated. The families were confirmed as experiencing stigma: labeling, stereotyping, separation and discrimination. Stigma means that the families face psychological, social and intrapersonal consequences which can reduce the family quality of life and family functioning.Conclusion: There are opportunities for negative outcomes related to the family resilience. One of the results of the study revealed that psycho-education programs using education interventions can be an alternative intervention to reduce stigma.